Primers from the isoepoxydon dehydrogenase gene of the patulin biosynthetic pathway to indicate critical control points for patulin contamination of apples - Paterson, R. R. M. (2006)
The mycotoxin patulin is subjected to European Union statutory limits, and has action levels imposed in the United States of America in fruit products. Samples from soil and an orchard were analysed by primers of the isoepoxydon dehydrogenase gene of the patulin biosynthetic pathway as an HACCP procedure in an initial assessment. A non-orchard soil appeared to inhibit the reaction. However, the reaction was positive from orchard soils. Negative results from orchard samples appeared to be because of target DNA being absent. Bramley samples contained the gene frequently. The method may be useful in the determination of critical control points.